Synthesis of Novel Azo-Linked 5-Amino-Pyrazole-4-Carbonitrile Derivatives Using Tannic Acid–Functionalized Silica-Coated Fe3O4 Nanoparticles as a Novel, Green, and Magnetically Separable Catalyst - Pashaki, Farhad Sedighi; Nikpassand, Mohammad (Frontiers in Chemistry, 2021)
Tannic acid‐functionalized silica‐coated Fe3O4 nanoparticles (Fe3O4@SiO2@Tannic acid) were synthesized and characterized by Transmission Electron Microscope (TEM), Field Emission Scanning Electron Microscope (FE-SEM), X-ray powder diffraction (XRD), X-ray spectroscopy (EDX), Vibrating sample magnetometry (VSM) and Fourier Transform Infrared Spectroscopy (FT-IR). Fe3O4@SiO2@Tannic acid supply an environmentally friendly procedure for the synthesis of some novel 5-amino-pyrazole-4-carbonitriles through three-component grinding reaction of synthetized azo-linked aldehydes, malononitrile, and phenylhydrazine or p-tolylhydrazine in accordance with green chemistry rules. In the other study, this novel synthesized magnetically reusable catalyst was introduced as a new avenue for the synthesis of 5-amino-pyrazole-4-carbonitriles using the reaction between synthetized azo-linked aldehydes, malononitrile, and phenylhydrazine or p-tolylhydrazine. These compounds were obtained in high yields and short reaction times. The catalyst could be easily recovered and reused for six cycles with almost consistent activity. The structures of the synthesized 5-amino-pyrazole-4-carbonitrile compounds were confirmed by 1H NMR, 13C NMR and FTIR spectral data and elemental analyses.